Kreĭn space unitary dilations of Hilbert space holomorphic semigroups - Marcantognini Palacios, Stefania Alma María (2020)
The infinitesimal generator A of a strongly continuous semigroup on a Hilbert space is assumed to satisfy that B_β:=A−β is a sectorial operator of angle less than π/2 for some β≥0. If B_β is dissipative in some equivalent scalar product then the Naimark-Arocena Representation Theorem is applied to obtain a Kreiin space unitary dilation of the semigroup.